Game Theoretic Applications to Environmental and Natural Resource Problems - Sumaila, Ussif Rashid; Dinar, Ariel; Albiac, Jose (2012)
Game theory has been useful as an analytical framework for assessing environmental and resource regulations and policies. The papers in this volume provide the latest methodological and applied works in game theory to a wide range of natural and environmental resource problems such as fishing, grazing, pollution, climate change, water allocation, and stochastic production processes. The findings in the papers suggest that game theory is an effective tool for the analysis of the efficient use of shared natural resources; it can be used to identify stable agreements between parties to a resource conflict, and show how non-cooperation over global public goods/bads has a high social cost tag.